2013
DOI: 10.1111/php.12099
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Tyrosine Photoinduced by Pterin in Aqueous Solution

Abstract: Pterins, heterocyclic compounds widespread in biological systems, accumulate in the skin of patients suffering from vitiligo, a chronic depigmentation disorder. Pterins have been previously identified as good photosensitizers under UV-A irradiation. In this work, we have investigated the ability of pterin (Ptr), the parent compound of oxidized pterins, to photosensitize the oxidation of tyrosine (Tyr) in aqueous solutions. Tyr is an important target in the study of the photodynamic effects of UV-A radiation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 52 publications
(52 reference statements)
2
61
0
1
Order By: Relevance
“…P Å+ leads to the irreversible damage and degradation of the protein (reaction 2), whereas Ptr ÅÀ , under aerobic conditions, transfers one electron to O 2 regenerating Ptr and forming superoxide anion (O 2 ÅÀ ) (reaction 3), which, in turn, is converted into hydrogen peroxide (H 2 O 2 ) by spontaneous disproportionation (reaction 4) [22]. Moreover, it was demonstrated that Ptr is able to photosensitize the oxidation of free Trp and Tyr in aqueous solution [23,24]. In particular, the study of the photosensitization of Tyr revealed that dimers of Tyr, or dityrosine are formed [24].…”
Section: Introductionmentioning
confidence: 98%
“…P Å+ leads to the irreversible damage and degradation of the protein (reaction 2), whereas Ptr ÅÀ , under aerobic conditions, transfers one electron to O 2 regenerating Ptr and forming superoxide anion (O 2 ÅÀ ) (reaction 3), which, in turn, is converted into hydrogen peroxide (H 2 O 2 ) by spontaneous disproportionation (reaction 4) [22]. Moreover, it was demonstrated that Ptr is able to photosensitize the oxidation of free Trp and Tyr in aqueous solution [23,24]. In particular, the study of the photosensitization of Tyr revealed that dimers of Tyr, or dityrosine are formed [24].…”
Section: Introductionmentioning
confidence: 98%
“…In general, it is accepted that the photosensitization of proteins occurs mainly through the reactions of 1 O 2 with tryptophan (Trp), tyrosine (Tyr), histidine (His), methionine (Met) and cysteine (Cys) side-chains [7]. Nevertheless, in recent reports, it has been demonstrated that pterins photosensitize peptides [8,9], proteins [10,11] and their components [12][13][14] mainly through a type I mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused our attention on the chemical modifications of tyrosine (Tyr) and tryptophan (Trp) residues because these amino acids are particularly susceptible to a variety of oxidizing agents [26]. Moreover, the photosensitization of free Trp and Tyr by Ptr has previously been reported [12,13]. The most relevant results, from a biological point of view, are summarized and discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations